Entre histórias e memórias: o pensamento histórico e as narrativas sobre a regionalidade na educação básica do Vale do Taquari - RS - Nicolini, Cristiano (2019)
Historical knowledge presents specificities that stimulate investigations about its nature and its function in society. Unlike the natural sciences, it is built on social interaction, over time and in defined spaces. Without this information, you run the risk of naturalizing it and emptying history of its explanatory and transformative potential. In this sense, the German thinker Jörn Rüsen (2001; 2006; 2015) proposes a Theory of History that locates this field of knowledge, explaining its particularities and the different dimensions in which it acts in reality. Through his investigations, the historian approached a group of thinkers linked to the so-called Historical Education, which emerged in the 1970s in Europe, and today operates in various countries of that continent and also America. This thesis starts from the presuppositions of this research line to understand the relations between the narratives about regionality present in the territory called Vale do Taquari, located in the center-east portion of the state of Rio Grande do Sul, Brazil, and the formation of the historical thinking of young people attending basic education in the thirty-six municipalities in this region. The fieldwork involved visiting schools in these administrative units, in which an interview was conducted with students of the 9th grade of elementary school, completing the first stage of basic education. In this process, each group of students was presented with a set of images corresponding to their municipality, followed by three questions about local and regional history. From this work, a total of 542 interviews were gathered, including young people from 13 to 18 years old, all enrolled and attending this stage of schooling. Starting from the references of Historical Education (Barca, 2001; Lee, 1994; Fronza, 2012; Cainelli, 2017; Cunha, 2017; Martins, 2017), a table was elaborated with categories corresponding to the historical ideas present in the narratives of these students: presentist, ethnocentric, multicultural and intercultural. From these empirical data, we sought to understand the relationship between the process of heritage patrimonialization triggered in the territory and the learning that these young people develop in school life, so that the limits and possibilities of curricular proposals in the interaction with the children are understood different influences on the formation of knowledge and historical consciousness of the subjects.